Massacres in the Arnsberg Forest (an abstract) - Michael Baales; Marcus Weidner; Manuel Zeiler (Internet Archaeology, 2024)
In the Arnsberg Forest near Warstein and Meschede (southern Westphalia, western Germany), 208 forced labourers were massacred by the 'Division for Vengeance' (Division zur Vergeltung) of SS General Hans Kammler in March 1945. In the course of this joint project, archaeological research conducted by the Olpe Department of the LWL-Archäologie für Westfalen (Westphalian Archaeological Heritage Service) has pinpointed the exact location of the crime scenes and provided clues for the reconstruction of the course of events in the field (Warstein Langenbachtal, Suttrop, Meschede-Eversberg). It has also enabled the recovery of finds belonging to both the victims and perpetrators.